2019
DOI: 10.1111/1758-2229.12742
|View full text |Cite
|
Sign up to set email alerts
|

The entomopathogenic fungus Beauveria bassiana produces microsclerotia‐like pellets mediated by oxidative stress and peroxisome biogenesis

Abstract: Summary Several filamentous fungi are known to produce macroscopic pigmented hyphal aggregates named sclerotia. In recent years, some entomopathogenic fungi were reported to produce small sclerotia termed ‘microsclerotia’, becoming new potential propagules for biocontrol strategies. In this study, we described the production of microsclerotia‐like pellets by the entomopathogenic fungus Beauveria bassiana. The carbon: nitrogen ratio equal to or higher than 12.5:1 amended with Fe2+ induced the germination of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 31 publications
3
14
0
6
Order By: Relevance
“…B. bassiana assimilate variable amounts of fatty alcohols, fatty acids and wax esters in the host cuticles (Pedrini et al, 2010). When conidia develop into microsclerotia-like pellets, peroxisome proliferation as well as peroxisomal peroxidase activity is significantly enhanced (Huarte- Bonnet et al, 2019). However, the roles of peroxisome and Pex genes in physiologies of B. bassiana are still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…B. bassiana assimilate variable amounts of fatty alcohols, fatty acids and wax esters in the host cuticles (Pedrini et al, 2010). When conidia develop into microsclerotia-like pellets, peroxisome proliferation as well as peroxisomal peroxidase activity is significantly enhanced (Huarte- Bonnet et al, 2019). However, the roles of peroxisome and Pex genes in physiologies of B. bassiana are still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…In Metarhizium robertsii (a sister entomopathogenic fungus), peroxisomal activity and peroxin genes are involved in fungal responses to oxidative stress [ 38 ]. Under submerged conditions, Woronin bodies are involved in peroxisome biogenesis and the stress response in B. bassiana during microsclerotia formation [ 10 ]. In insect hemocoel, hemolymph causes osmotic stress on fungal cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In filamentous fungi, peroxisomes have important roles in secondary metabolism [ 7 ], development [ 8 ], and pathogenicity [ 9 ]. Similarly, peroxisomes are involved in fatty-acid assimilation, stress response, development, and virulence in B. bassiana [ 10 , 11 ]. Our previous study showed the functional divergence of different peroxins and highlighted the essential roles of peroxisomes involved in biocontrol potential of the entomopathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Beauveria bassiana es una especie ampliamente distribuida, este hongo se considera ubicuo capaz de explotar una variedad de entornos, incluidos el suelo, las plantas y los insectos; puede vivir como un saprófito en el suelo, o como un entomopatógeno que afecta a una amplia gama de artrópodos (Zimmerman, 2007;Boomsma et al, 2014). B. bassiana presenta diferentes tipos de propágulos, específicamente, conidios, blastosporas y microesclerocios (Mascarin et al, 2015;Huarte-Bonnet et al, 2019). B. bassiana actualmente se comercializa como ingrediente activo en diferentes micoinsecticidas, ocupando un 33.9% del mercado aproximadamente, y son los conidios aéreos el ingrediente activo principal de estos productos (de Faria & Wraight, 2007).…”
Section: Introductionunclassified